TEACHERS' AND STUDENTS' VIEWS ON ECONOMIC LEARNING USING DIGITAL COMIC MEDIA FOR STUDENTS - Akhmad Hanafi Maulana (Universitas Lambung Mangkurat, 2026)
The rapid development of information and communication technology has increased the need for innovative learning approaches in education. This study aims to analyze teachers’ and students’ perspectives on Economics learning using digital comic media in the topic of International Trade for eleventh-grade students at SMAN 4 Banjarmasin, as well as to identify the supporting and inhibiting factors in its implementation. This research employed a descriptive qualitative approach with the principal, Economics teachers, and eleventh-grade students as research subjects. Data were collected through structured interviews, observation, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing or verification. The results show that both teachers and students perceive digital comic media as an effective and relevant learning medium for bridging abstract International Trade concepts through contextual visual and narrative presentations, thereby enhancing students’ understanding, motivation, and participation. Supporting factors include school support, teacher readiness, and the characteristics of digital-native students, while inhibiting factors consist of limited internet access, technical constraints, and teachers’ workload in developing digital learning media.